2020
DOI: 10.18632/aging.102937
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin protects chondrocytes against IL-18-induced apoptosis and ameliorates rat osteoarthritis

Abstract: Interleukin 18 (IL-18) promotes inflammation and apoptosis in chondrocytes, thereby contributing to the development and progression of osteoarthritis (OA). Here, we investigated the effects of IL-18 treatment and inhibition in rat chondrocytes in vitro and in vivo. We used RT-PCR and Western blotting to measure the mRNA and protein levels of the chondrocyte-specific genes Collagen II and Aggrecan as well as the protein levels of apoptosis-related (Bax, Bcl2, Caspase3/9), autophagy-related (Atg5, Atg7, Beclin1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 36 publications
(44 reference statements)
3
62
0
1
Order By: Relevance
“…However, treatment with rapamycin significantly alleviated the pathological changes in the articular cartilage and head, and, notably, with an increase in icariin concentration, the pathological changes in the articular cartilage and head were ameliorated in a dose-dependent manner. The alleviation effect of rapamycin was also reported by Bao [34].…”
Section: Icariin Ameliorated Pathological Symptoms In Oa Ratssupporting
confidence: 73%
See 1 more Smart Citation
“…However, treatment with rapamycin significantly alleviated the pathological changes in the articular cartilage and head, and, notably, with an increase in icariin concentration, the pathological changes in the articular cartilage and head were ameliorated in a dose-dependent manner. The alleviation effect of rapamycin was also reported by Bao [34].…”
Section: Icariin Ameliorated Pathological Symptoms In Oa Ratssupporting
confidence: 73%
“…Furthermore, the results of immunofluorescence and western blotting assays (Figure 6(b,c)) showed that ATG7 and LC3-II/LC3-I levels were markedly lower in the OA group than in the sham group, but the levels were significantly upregulated after rapamycin treatment and increased in a dose-dependent manner after icariin treatment (**p < 0.01 vs. sham, ##p < 0.01 vs. OA). The autophagy-inducing effect of rapamycin in OA cartilage tissues has also been reported by Bao [34].…”
Section: Icariin Activated Autophagy In Cartilage Tissuessupporting
confidence: 63%
“…Rapamycin was first approved in 1999 for allograft protection in kidney transplant recipients and approved in 2002 for the antirestenosis aspect for patients with coronary artery repairs [ 21 ]. In recent years, interests of rapamycin have been drawn to its potential as an anticancer drug, as well as its beneficial effects shown in a number of animal models of neurodegeneration and osteoarthritis [ 22 , 23 ]. Moreover, researchers have found the association of the mTOR pathway signaling activity with cellular and organismal aging [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…IL-18, another cytokine processed by the NLRP3 inflammasome, is elevated in synovial fluid and serum of patients with OA, and has been proven to decrease type II collagen and aggrecan expression, disrupt autophagy and induce apoptosis in chondrocytes ( 230 , 231 ). A recent work shows that inhibition of the mTOR pathway after IL-18 treatment has protective effects in chondrocytes both in vitro and in vivo ( 232 ). Data suggest that IL-1β and IL-18 are mainly produced in the damaged synovium rather than cartilage ( 233 ).…”
Section: Purinergic System In Oa and Modulation By Metainflammationmentioning
confidence: 99%